Non-suicidal self-injury in adolescence: a validation of the Chinese version of the Inventory of Statements About Self-Injury in student populations - Xinhe Tian; Xinhe Tian; Hebin Huang; Hebin Huang; Weicong Lu; Weicong Lu; Ruoxi Zhang; Ruoxi Zhang; Runhua Wang; Runhua Wang; Xiaoyue Li; Xiaoyue Li; et al. (Frontiers in Psychiatry)
BackgroundThe Inventory of Statements About Self-Injury (ISAS) is a widely utilized scale for evaluating the 13 potential functions that motivate non-suicidal self-injury(NSSI) behaviors. However, its validation for assessing such motivation in a Chinese context is still lacking.AimsThe main objective was to access the validation of ISAS as an instrument in Chinese young population.MethodA total of 1,106 completed online self-report questionnaires were collected, with 167 reporting a history NSSI. The age range of these individuals was 12 to 24 years old, comprising 74 female and 93 male participants. The factor structure and construct validity were calculated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The correlations of the Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder-7 (GAD-7), the Brief Self-Control Scale (BSCS), the Self-Rating Idea of Suicide Scale (SIOSS), and the Chinese version of the ISAS were tested using bivariate correlation analyses.ResultsThe internal consistencies of the Chinese version of the ISAS were good to excellent, with 0.788- 0.950 and 0.80-0.949 in the sports group and the junior high school group, respectively. EFA and CFA exhibited a good two-factor structure model (NFI = 0.942, CFI = 0.974, IFI = 0.974, RMSEA = 0.068, SRMR = 0.043, CMIN/DF = 1.762). Moreover, the scores of the functions of the ISAS were correlated with depression (r=0.208, p<0.01), anxiety (r=0.223, p<0.01), suicidal ideation (r=0.322, p<0.01), and low self-control (r=-0.230, p<0.01).ConclusionThis study validates the Chinese ISAS as a reliable NSSI measure, identifies a two-factor structure, and aims to inform targeted interventions and future research on self-injury behaviors among Chinese adolescents.